2013
DOI: 10.1556/jba.1.2012.012
|View full text |Cite
|
Sign up to set email alerts
|

Cue reactivity towards shopping cues in female participants

Abstract: Background and aims: It is currently under debate whether pathological buying can be considered as a behavioural addiction. Addictions have often been investigated with cue-reactivity paradigms to assess subjective, physiological and neural craving reactions. The current study aims at testing whether cue reactivity towards shopping cues is related to pathological buying tendencies. Methods: A sample of 66 non-clinical female participants rated shopping related pictures concerning valence, arousal, and subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
4
24
1
Order By: Relevance
“…computer, home environment) stimuli with the reinforcing effects of cybersex resulting in cue-reactivity and craving reactions, associated to repeated cybersex use elicited by conditioned stimuli. This is in line with literature on other behavioral and substance addictions (Braus et al, 2001;Garavan, Pankiewicz & Bloom, 2000;Goudriaan, De Ruiter, Van den Brink, Oosterlaan & Veltman, 2010;Gray, LaRowe & Upadhyaya, 2008;Grüsser et al, 2004;Ko et al, 2009;Parker & Gilbert, 2008;Starcke, Schlereth, Domaß, Schöler & Brand, 2012;Thalemann, Wölfling & Grüsser, 2007;Yang et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…computer, home environment) stimuli with the reinforcing effects of cybersex resulting in cue-reactivity and craving reactions, associated to repeated cybersex use elicited by conditioned stimuli. This is in line with literature on other behavioral and substance addictions (Braus et al, 2001;Garavan, Pankiewicz & Bloom, 2000;Goudriaan, De Ruiter, Van den Brink, Oosterlaan & Veltman, 2010;Gray, LaRowe & Upadhyaya, 2008;Grüsser et al, 2004;Ko et al, 2009;Parker & Gilbert, 2008;Starcke, Schlereth, Domaß, Schöler & Brand, 2012;Thalemann, Wölfling & Grüsser, 2007;Yang et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…CBD has also been conceptualized as a form of obsessive–compulsive disorder, and thus, CBD has been characterized as existing on the impulsive–compulsive spectrum (Frost, Kim, Morris, Bloss, & Murray-Close, 1998). More recently, research has indicated correlates of behavioral addictions like cue reactivity and cravings (Starcke, Schlereth, Domass, Schöler, & Brand, 2013; Trotzke, Starcke, Pederson, & Brand, 2014), adding further debate to the categorization of CBD.…”
Section: Background and Aimsmentioning
confidence: 99%
“…However, given that compulsive buyers are especially prone to advertising (Mikołajczak-Degrauwe and Brengman, 2014) and over-reactive to shopping-related cues (Starcke et al, 2013) it is reasonable to suppose that the prevalence of CBD is higher in shopping mall visitors than in the general population. In line with these expectations, Phau and Woo (2008) found that over one-third (37%) of Australian shopping mall visitors were classified as CBD based on the Compulsive Buying Scale (CBS, Faber and O'Guinn, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…CBD is listed as "shopping addiction" in the appendix of the most recent version of The Diagnostic and Statistical manual of Mental Disorders (DSM-5, APA), but it is not a recognised as a distinct mental disorder due to insufficient evidence to establish the diagnostic criteria (American Psychiatric Association, 2013). Nonetheless, CBD is considered by many to constitute a behavioural addiction (Demetrovics and Griffiths, 2012;Lo and Harvey, 2012;Rose and Dhandayudham, 2014;Starcke et al, 2013). Like most addictive disorders, compulsive buying is characterised by both impulsive and compulsive aspects (Christenson et al, 1994;McElroy et al, 1994).…”
Section: Introductionmentioning
confidence: 99%